Management of Housewive, 57 Years Old With Uncontrolled Type 2 of Diabetes Melitus Through Family Medicine Approach in Karang Anyar Health Center 2022 - Anthia Vradinatika; Reni Zuraida (Majority, 2023)
Type 2 diabetes mellitus (DM) is a non-communicable disease known as a silent killer with a prevalence of 9.3% of the totalpopulation in the world and 10.7% of the total population in Indonesia according to the International Diabetes Federation(IDF). ) in 2019. The research objective is to implement evidence-based medicine-based family doctor services by identifyingrisk factors, clinical problems and patient management based on a patient-centered and family-centered problem-solvingframework. This study is a case report. Assessment is formulated based on the initial holistic diagnosis, process, and the endof the study qualitatively and quantitatively. The problems found in this case are related to the wrong perceptions of patientsand their families, inappropriate lifestyles, eating patterns and physical activity as well as the lack of support and motivationof family members. After holistic and comprehensive management was carried out, there was an increase in patient andfamily knowledge points about DM from 40 to 90, and a temporary decrease in blood sugar levels from 540 mg/dL to 271mg/dL.